Clinical applications of 3D volume MR imaging of the fetal brain in utero. (15th May 2017) - Jarvis, Deborah; Griffiths, Paul D.
Abstract: Objective: In our earlier publication, we described the methods of acquiring 3D volume MR data in second and third trimester fetuses and provided normative data from a large cohort of normal fetuses. In this article, we show the applicability of the technique by describing five fetuses with a range of developmental brain abnormalities. Methods: The five cases described in this report all had an intra‐cranial abnormality recognised on prenatal ultrasonography, which precipitated referral for in utero MR imaging. This consisted of routine ultrafast 2D sequences and 3D volume imaging acquired using balanced steady‐state imaging (Fast Imaging Employing Steady‐state Imaging – FIESTA). The 3D data were used to reconstruct models of the fetal brains and hence derive representations of the surfaces of the brain and estimates of volumes of the intracranial compartments. Case studies: These cases show several important features of relevance for diagnosing intracranial fetal pathology. Conclusions: 3D volume in utero MR imaging appears to be a promising method in the prenatal assessment of the fetal brain. We propose possible areas of future research that are required to assess the techniques potential to have clinical impact. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? In utero MR imaging has improved diagnostic accuracy in detecting fetal brain abnormalities. There is often a disconnect between the size of the fetal skull and the size of the fetal brain; specifically, the fetal brain is frequently found to be abnormally small in spite of normal skull sizes. What does this study add? There is a need to measure all of the intracranial compartments (external CSF spaces, brain parenchyma and CSF in the ventricular system) separately in order not to make diagnostic errors. 3D models have the potential to improve diagnostic accuracy and confidence further.